Faktor-Faktor yang Berhubungan dengan Kebiasaan Sarapan Siswa pada SDN Sungai Rangas Hambuku Martapura Barat - Octaviani, Yulia; Rachmawati, Kurnia; Santi, Eka (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
In Indonesia, a lot of people aren’t used to having breakfast, report Riskesdas 2010 16,9%-50% school-agechildren in Indonesia weren’t used to having breakfast, consumption of 35.000 elementary school-age children26,1% of drink for breakfast and 44,6% had less than 15% nutritional adequency rate of energy intake. Thepurpose of this study was analyze factors related to breakfast habit of students in SDN Sungai Rangas Hambuku,West Martapura. The present study used descriptive correlational research design with cross sectionalapproach. Research population were all 4th and 5th grade students with sample of 44 respondents collectedtechnique with proportional stratified random sampling. Analysis data used spearman rho correlation. Resultsthis study found there was no significant relation between gender (p=0.509), education of mother (p=0.117),occupation of mother (p=0.954), family encouragement (p=0.441), availability of breakfast at home (p=0.614),peer (p=0.398), allowance (p=0.979) to breakfast habit.